Method for producing a propylene polymer composition
Patent Information
- Application Number
- JP2022014772
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2022-02-02
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2042-02-02
AI Technical Summary
【0009】 本発明のプロピレン系重合体組成物の製造方法は、プロピレン·エチレン共重合体とエチレン·α-オレフィン共重合体を含むプロピレン系重合体組成物を一括で製造でき、且つ、当該製造方法で得られた組成物からなる成形体は、透明性、耐衝撃性、剛性に優れ、フレーム処理後の透明性が維持できる。
Smart Images

Figure 0007933501000001 
Figure 0007933501000002
Abstract
Description
[Technical Field]
[0001] A method for producing a propylene polymer composition suitable for obtaining injection-molded articles with excellent transparency, impact resistance, and rigidity. [Background technology]
[0002] Polyolefins (olefin polymers), such as polyethylene and polypropylene, are attracting increasing attention in various industries as part of their efforts to create a circular economy through the 3Rs (Reduce, Reuse, Recycle), due to their low energy production requirements, lightweight nature, and excellent recyclability. Polyolefins are used in a wide range of fields, including daily necessities, kitchenware, packaging films, home appliances, machine parts, electrical components, and automotive parts.
[0003] Among olefin polymers, polypropylene has excellent rigidity and heat resistance, but is inferior to polyethylene in cold resistance and impact resistance. Therefore, as a method to improve the physical properties of molded articles such as films obtained from polypropylene, a polypropylene resin composition is proposed in which polyethylene (ethylene-α-olefin copolymer) is blended with polypropylene (Patent Document 1).
[0004] On the other hand, while the impact resistance is improved by blending polypropylene with ethylene-α-olefin copolymer, transparency may decrease. Therefore, a method has been proposed (Patent Document 2) in which, when adding an organic peroxide (D) to propylene-ethylene random copolymer (A), ethylene-α-olefin copolymer (B), and propylene homopolymer (C), components (A) and (B) are melt-kneaded separately, and then the two are melt-kneaded together to obtain a propylene resin composition. [Prior art documents] [Patent Documents]
[0005] [Patent Document 1] Japanese Patent Publication No. 2016-108509 [Patent Document 2] Japanese Patent Publication No. 2004-176061 [Overview of the project] [Problems that the invention aims to solve]
[0006] The technology described in Patent Document 2 requires two steps to produce the composition, as it does not simultaneously perform the kneading to atomize the ethylene-α-olefin copolymer (B) and the kneading to reduce the propylene-ethylene random copolymer (A) with an organic peroxide, but rather uses a sequential melt kneading or divided melt kneading method to control the dispersed phase to a fine dispersion state. Furthermore, the transparency after flame treatment has not been sufficiently considered.
[0007] The object of the present invention is to develop a method for producing a propylene-based polymer composition that is suitable for obtaining a molded article with excellent transparency, impact resistance, and rigidity, and that retains good transparency even after frame treatment, by compounding an organic peroxide with a specific propylene-ethylene copolymer and a specific ethylene-α-olefin copolymer and performing dynamic heat treatment in a single step. [Means for solving the problem]
[0008] The present invention relates to the following [1] to [4]. [1] Ethylene content of 1-5% by mass, melt flow rate (MFR) conforming to JIS K7210 (temperature: 230°C, 2.16 kg load). A 80 to 91 parts by mass of propylene-ethylene copolymer (A) having a concentration in the range of 0.1 to 50 g / 10 min, And the density is 890-909 g / cm³ 3 Melt flow rate (MFR) conforming to JIS K7210 (temperature: 190℃, 2.16kg load) B A mixture containing 9 to 20 parts by mass of ethylene-α-olefin copolymer (B) having a concentration in the range of 1 to 50 g / 10 min [provided that the total amount of (A) + (B) is 100 parts by mass], A dynamic heat treatment is performed with an organic peroxide, and the melt flow rate (MFR) conforming to JIS K7210 (temperature: 230°C, load: 2.16 kg) C ) satisfies the following formula 1, and is in the range of 1 to 100 g / min, a method for producing a propylene-based polymer composition (C). (MFR C )-(MFR A )≦2×(MFR B )···Formula (1) [2] The method for producing the propylene-based polymer composition (C) according to item [1], wherein the mixture contains a nucleating agent. [3] An injection-molded article comprising the propylene-based polymer composition (C) according to item [1] or [2]. [4] The injection-molded article according to item [3], which is obtained by subjecting the injection-molded article to flame treatment. [Effects of the Invention]
[0009] The method for producing a propylene-based polymer composition of the present invention enables collective production of a propylene-based polymer composition containing a propylene-ethylene copolymer and an ethylene-α-olefin copolymer, and a molded article formed from the composition obtained by the production method is excellent in transparency, impact resistance and rigidity, and can maintain transparency after flame treatment. [Modes for Carrying Out the Invention]
[0010] Hereinafter, the modes for carrying out the present invention will be described. <Propylene-ethylene copolymer (A)> The propylene-ethylene copolymer (A), which is one of the raw materials of the propylene-based polymer composition (C) according to the present invention, has an ethylene content of 1 to 5% by mass, preferably 1.5 to 3.5% by mass, and a melt flow rate (MFR) conforming to JIS K7210 (temperature: 230°C, load: 2.16 kg) A ) of 0.1 to 50 g / 10 min, preferably 0.4 to 30 g / 10 min, and is a random copolymer of propylene and ethylene.
[0011] A propylene homopolymer or a copolymer having an ethylene content of less than 1 mass% may lead to poor impact resistance and transparency of a molded article formed from the propylene-based polymer composition, whereas a copolymer having an ethylene content exceeding 5 mass% may lead to poor rigidity of a molded article formed from the propylene-based polymer composition.
[0012] The production method of the propylene-ethylene copolymer (A) according to the present invention is not particularly limited, and known methods using well-known catalysts such as Ziegler-Natta catalysts and metallocene-based catalysts can be mentioned.
[0013] <Ethylene / α-olefin Copolymer (B)> The ethylene / α-olefin copolymer (B), which is one of the raw materials of the propylene-based polymer composition (C) according to the present invention, has a density of 890 to 909 kg / m 3 , preferably 892 to 905 kg / m 3 and is a random copolymer of ethylene and an α-olefin.
[0014] A copolymer with a density of less than 890 kg / m 3 or 910 or more kg / m 3 has a large difference in refractive index between the propylene-ethylene copolymer (A) and the ethylene / α-olefin copolymer, visible light is diffusely reflected on the surface of the copolymer dispersed in an island shape in the propylene-ethylene copolymer (A), and there is a risk that the transparency of a molded article formed from the propylene-based polymer composition will decrease.
[0015] It is a random copolymer of ethylene and an α-olefin having a melt flow rate (MFR) in accordance with JIS K7210 (temperature: 190°C, 2.16 kg load) B of 1 to 50 g / 10min, preferably 3 to 30 g / 10min.
[0016] MFR BCopolymers with a flow rate of less than 1 g / 10 min exhibit poor fluidity, resulting in poor moldability of the resulting propylene-based polymer composition. Furthermore, the dispersion particle size of the ethylene-α-olefin copolymer may increase, potentially reducing transparency. (MFR) B Copolymers with a concentration exceeding 50 g / 10 min may have reduced impact resistance in molded articles made from propylene polymer compositions.
[0017] The α-olefin copolymerized with ethylene preferably has a number of carbon atoms. 4 It is an α-olefin of ~20, specifically 、1 Examples include butene, 4-methyl-1-pentene-1, 1-hexene, 1-heptene, 1-octene, 1-nonene, 1-decene, 1-undecene, 1-dodecene, 1-tridecene, 1-tetradecene, 1-pentadecene, 1-hexadecene, 1-heptadecene, 1-nonadecene, 1-eicosene, 9-methyl-1-decene, 11-methyl-1-dodecene, and 12-ethyl-1-tetradecene. These α-olefins can be used individually or in combination of two or more.
[0018] The method for producing the ethylene-α-olefin copolymer (B) according to the present invention is not particularly limited, and includes well-known methods using well-known catalysts such as Ziegra-Natta catalysts and metallocene catalysts.
[0019] <Organic peroxide> The organic peroxide used in producing the propylene polymer composition (C) according to the present invention is a known compound, specifically including benzoyl peroxide, dichlorobenzoyl peroxide, dicumyl peroxide, di-tert-butyl peroxide, 2,5-dimethyl-2,5-di(peroxidebenzoate)hexine-3, 1,4-bis(tert-butylperoxyisopropyl)benzene, lauroyl peroxide, tert-butyl peracetate, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexine-3, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, tert-butyl perbenzoate, tert-butyl perphenyl acetate, tert-butyl perisobutyrate, tert-butyl per-sec-octoate, tert-butyl perpivalate, cumyl perpivalate, and tert-butyl perdiethyl acetate.
[0020] <Nucleating agent> The nucleating agents that can be added when producing the propylene polymer composition (C) according to the present invention are compounds that promote the crystallization of the propylene-ethylene random copolymer (A) and ethylene-α-olefin copolymer (B) contained in the raw materials, and are also called crystal nucleating agents or nucleating agents. Specifically, examples include sodium benzoate, bisbenzylidene sorbitol, bis(p-methylbenzylidene) sorbitol, bis(p-ethylbenzylidene) sorbitol, sodium-2,2-methylenebis(4,6-di-t-butylphenyl) phosphite, talc, titanium dioxide, aluminum hydroxydi-pt-butylbenzoate, aromatic phosphate ester salts, aromatic carboxylic acids, nonitol-based nucleating agents such as D-glycero-L-globonitol, 7,8,9-trideoxy-3,5:45-bis-O-[(R-propylphenyl)methylene], and rosin-based nucleating agents, which can be used alone or in combination of two or more.
[0021] When producing the propylene polymer composition according to the present invention, in addition to the above-mentioned organic peroxide and crystal nucleating agent, known additives such as antioxidants, ultraviolet absorbers, neutralizing agents, light stabilizers, antistatic agents, antiblocking agents, lubricants, odor adsorbents, antibacterial agents, pigments, inorganic and organic fillers, and various synthetic resins may be added as needed, provided that the objectives of the present invention are not impaired.
[0022] ≪Method for producing propylene polymer composition (C)≫ The method for producing the propylene polymer composition (C) of the present invention involves preparing a mixture containing 80 to 91 parts by mass, preferably 85 to 90 parts by mass, of the above-mentioned propylene-ethylene copolymer (A), and 9 to 20 parts by mass, preferably 10 to 15 parts by mass, of the above-mentioned ethylene-α-olefin copolymer (B) [provided that the total amount of (A) + (B) is 100 parts by mass], Dynamic heat treatment with organic peroxides is performed to obtain a melt flow rate (MFR) in accordance with JIS K7210 (temperature: 230°C, 2.16 kg load). C ) satisfies formula 1 below, and 1 to 100g / 10 This is a method for obtaining a propylene-based polymer composition (C) in the range of min. (MFR C )-(MFR A )≦2×(MFR B )...Equation (1)
[0023] If the amount of ethylene-α-olefin copolymer (B) is less than 9 parts by mass, the molded article made from the composition may have poor impact resistance, while a molded article made from more than 20 parts by mass of the composition may have poor rigidity.
[0024] The magnitude of the increase in MFR of propylene-ethylene copolymer (A) can be adjusted by the amount of organic peroxide added and the dynamic heat treatment time. Furthermore, even when ethylene-α-olefin copolymer (B) is subjected to dynamic heat treatment with organic peroxide, the increase in MFR is not significant. Therefore, in the present invention, the above formula (1) can be satisfied by appropriately selecting the MFR and blending ratio of propylene-ethylene copolymer (A) and ethylene-α-olefin copolymer (B), the amount of organic peroxide added, and the dynamic heat treatment time.
[0025] Furthermore, the melt flow rate (MFR) of the obtained propylene polymer composition (C) C ) and the melt flow rate (MFR) of propylene-ethylene copolymer (A), which is one of the raw materials. A The difference (change) between ) and the melt flow rate (MFR) of ethylene-α-olefin copolymer (B), one of the raw materials. B The relationship between ( ) satisfies the above formula (1), resulting in a molded article obtained from the propylene polymer composition (C) having superior impact resistance, and the transparency of the molded article does not decrease even when it is framed.
[0026] In the method for producing the propylene polymer composition (C) of the present invention, the amount of organic peroxide added (amount blended) can be appropriately determined by the MFR of the obtained propylene polymer composition (C), the MFR of the raw materials propylene-ethylene random copolymer (A) and ethylene-α-olefin copolymer (B), and their blending ratio. However, it is usually in the range of 0.005 to 0.5 parts by mass per 100 parts by mass of the total amount of propylene-ethylene random copolymer (A) and ethylene-α-olefin copolymer (B).
[0027] The propylene polymer composition (C) obtained by the production method of the present invention is melt flow rate (MFR) in accordance with JIS K7210 (temperature: 230°C, 2.16 kg load). c The MFR is in the range of 1 to 100 g / 10 min, preferably 2 to 60 g / 10 min, and more preferably 3 to 40 g / 10 min. cIf the ratio is less than 1 g / 10 min, the fluidity of the propylene polymer composition is poor, which may lead to poor moldability. c If the concentration exceeds 100 g / 10 min, there is a risk that the impact resistance of the molded article made of the propylene polymer composition will decrease.
[0028] <Molded body> The propylene polymer composition obtained by the manufacturing method of the present invention has excellent moldability, and therefore can be molded using a variety of molding methods.
[0029] Specific examples of the molded articles of the present invention include injection molded articles, foamed molded articles, injection foamed molded articles, injection blow molded articles, extruded articles, blow molded articles, vacuum / pressure molded articles, calendered articles, stretched films, and inflation films. Injection molded articles are particularly preferred. The molding conditions when manufacturing the molded articles are not particularly limited, and known conditions can be used.
[0030] The molded article of the present invention, by frame treatment, makes the surface of a propylene-based resin composition, which normally has poor adhesion and insufficient peel strength when labeled or printed, hydrophilic, thereby enabling labeling and printing.
[0031] A molded article made from a propylene-based polymer composition according to the present invention has the characteristic that the transparency of the molded article does not decrease even after flame treatment. The flame treatment of a molded body according to the present invention is a method of applying oxygen plasma to a workpiece by burning a mixture of combustion gas and air using a flame treatment machine to convert oxygen in the air into plasma, thereby making the surface of the molded body hydrophilic.
[0032] The applications of the molded articles of the present invention are not particularly limited. Specific examples of preferred applications include distribution materials such as containers and pallets, automotive interior and exterior components such as door panels, pillar trims, door trims, door lower garnishes, and instrument panels, engine compartment components, other automotive parts, daily necessities, home appliance components, food containers, beverage containers, and medical containers. Among these, applications as distribution materials are preferred, and applications as containers are particularly preferred. [Examples]
[0033] The present invention will be described in more detail below based on examples, but the present invention is not limited in any way to these examples. The propylene-ethylene random copolymer (A), ethylene-α-olefin copolymer (B), and ethylene-α-olefin copolymer (E) used in the examples and comparative examples are shown below.
[0034] [Propylene-ethylene random copolymer (A-1)] <Production of propylene-ethylene random copolymer (A-1)> (1) Preparation of solid catalyst components 95.2 g of anhydrous magnesium chloride, 442 mL of decane, and 390.6 g of 2-ethylhexyl alcohol were heated at 130°C for 2 hours to form a homogeneous solution. Then, 21.3 g of phthalic anhydride was added to this solution, and the mixture was stirred at 130°C for 1 hour to dissolve the phthalic anhydride.
[0035] The homogeneous solution thus obtained was cooled to room temperature, and then 75 mL of this homogeneous solution was added dropwise over 1 hour to 200 mL of titanium tetrachloride, which was kept at -20°C. After the addition was complete, the temperature of this mixture was raised to 110°C over 4 hours, and when it reached 110°C, 5.22 g of diisobutyl phthalate (DIBP) was added, and the mixture was stirred and held at the same temperature for 2 hours.
[0036] After the 2-hour reaction was complete, the solid was collected by thermal filtration, resuspended in 275 mL of titanium tetrachloride, and then heated again at 110°C for 2 hours. After the reaction was complete, the solid was again collected by thermal filtration and thoroughly washed with decane and hexane at 110°C until no free titanium compounds were detected in the solution.
[0037] The detection of the free titanium compound was confirmed by the following method. 10 mL of the supernatant of the solid catalyst component was taken with a syringe and placed into a 100 mL Schlenk flask with a branch, which had been pre-purged with nitrogen. Next, the solvent hexane was dried under a nitrogen stream, and then vacuum-dried for 30 minutes. 40 mL of deionized water and 10 mL of 50% sulfuric acid were added, and the mixture was stirred for 30 minutes. This aqueous solution was transferred to a 100 mL volumetric flask through filter paper, and then 1 mL of concrete H3PO4 as a masking agent for iron(II) ions and 5 mL of 3% H2O2 aqueous solution as a titanium colorimetric reagent were added, and the volume was further increased to 100 mL with deionized water. The volumetric flask was shaken, and after 20 minutes, the absorbance at 420 nm was observed using UV light to detect free titanium. Washing and detection of free titanium were repeated until no further absorption was observed.
[0038] The solid titanium catalyst component (A) prepared as described above was stored as a decance slurry, and a portion of it was dried for the purpose of investigating the catalyst composition. The composition of the solid titanium catalyst component (A) obtained in this way was 2.3 mass% titanium, 61 mass% chlorine, 19 mass% magnesium, and 12.5 mass% DIBP.
[0039] (2) Preparation of prepolymerization catalyst components A 500 mL three-necked flask equipped with a stirrer was purged with nitrogen gas, and then 400 mL of dehydrated heptane, 19.2 mmol of triethylaluminum, 3.8 mmol of dicyclopentyl dimethoxysilane, and 4 g of the above solid titanium catalyst component (A) were added. The internal temperature was maintained at 20°C, and propylene was introduced while stirring. After 1 hour, stirring was stopped, and as a result, a prepolymerization catalyst component (B) was obtained in which 2 g of propylene polymerized per 1 g of solid titanium catalyst component (A).
[0040] (3) Polymerization A 10 L stainless steel autoclave with a stirrer was thoroughly dried and purged with nitrogen. Then, 6 L of dehydrated heptane, 12.5 mmol of triethylaluminum, and 0.6 mmol of dicyclopentyl dimethoxysilane were added. After purging the nitrogen in the system with propylene, hydrogen was charged at 0.03 MPa-G, and then propylene and ethylene were introduced while stirring. The amount introduced was adjusted so that the ethylene concentration in the gas phase of the polymerization tank was 2.3 mol%.
[0041] After the system stabilized at an internal temperature of 80°C and a total pressure of 0.8 MPa-G, 20.8 mL of heptane slurry containing 0.10 mmol of the above prepolymerization catalyst component (B) in terms of Ti atoms was added, and polymerization was carried out at 80°C for 3 hours while continuously supplying propylene. The resulting propylene polymer (A-1) is MFR A The concentration was 4.0 g / 10 min, and the ethylene content was 3.0 mass%.
[0042] [Propylene-ethylene random copolymer (A-2)] <Manufacturing of Propylene-Ethylene Random Copolymer (A-2)> Steps (1) and (2) are the same as those for the propylene-ethylene random copolymer polymer (A-1). (3) Polymerization A 10 L stainless steel autoclave with a stirrer was thoroughly dried and purged with nitrogen. Then, 6 L of dehydrated heptane, 12.5 mmol of triethylaluminum, and 0.6 mmol of dicyclopentyl dimethoxysilane were added. After purging the nitrogen in the system with propylene, hydrogen was charged at 0.01 MPa-G, and then propylene and ethylene were introduced while stirring. The amount introduced was adjusted so that the ethylene concentration in the gas phase of the polymerization tank was 1.8 mol%.
[0043] After the system stabilized at an internal temperature of 80°C and a total pressure of 0.8 MPa-G, 20.8 mL of heptane slurry containing 0.10 mmol of the above prepolymerization catalyst component (B) in terms of Ti atoms was added, and polymerization was carried out at 80°C for 3 hours while continuously supplying propylene. The obtained propylene-ethylene random copolymer (A-2) is MFR A The concentration was 0.5 g / 10 min, and the ethylene content was 2.5% by mass.
[0044] [Propylene-ethylene random copolymer (A-3)] <Manufacturing of Propylene-Ethylene Random Copolymer (A-3)> Steps (1) and (2) are the same as those for propylene-ethylene random copolymer (A-1). (3) Polymerization A 10 L stainless steel autoclave with a stirrer was thoroughly dried and purged with nitrogen. Then, 6 L of dehydrated heptane, 12.5 mmol of triethylaluminum, and 0.6 mmol of dicyclopentyl dimethoxysilane were added. After purging the nitrogen in the system with propylene, hydrogen was charged at 0.15 MPa-G, and then propylene and ethylene were introduced while stirring. The amount introduced was adjusted so that the ethylene concentration in the gas phase of the polymerization tank was 1.3 mol%.
[0045] After the system stabilized at an internal temperature of 80°C and a total pressure of 0.8 MPa-G, 20.8 mL of heptane slurry containing 0.10 mmol of the above prepolymerization catalyst component (B) in terms of Ti atoms was added, and polymerization was carried out at 80°C for 3 hours while continuously supplying propylene. The obtained propylene-ethylene random copolymer (A-3) is MFR A The concentration was 30 g / 10 min, and the ethylene content was 1.5% by mass.
[0046] [Propylene-ethylene random copolymer (A-4)] <Manufacturing of Propylene-Ethylene Random Copolymer (A-4)> Steps (1) and (2) are the same as those for propylene-ethylene random copolymer (A-1). (3) Polymerization A 10 L stainless steel autoclave with a stirrer was thoroughly dried and purged with nitrogen. Then, 6 L of dehydrated heptane, 12.5 mmol of triethylaluminum, and 0.6 mmol of dicyclopentyl dimethoxysilane were added. After purging the nitrogen in the system with propylene, hydrogen was charged at 0.07 MPa-G, and then propylene and ethylene were introduced while stirring. The amount introduced was adjusted so that the ethylene concentration in the gas phase of the polymerization tank was 2.3 mol%.
[0047] After the system stabilized at an internal temperature of 80°C and a total pressure of 0.8 MPa-G, 20.8 mL of heptane slurry containing 0.10 mmol of the above prepolymerization catalyst component (B) in terms of Ti atoms was added, and polymerization was carried out at 80°C for 3 hours while continuously supplying propylene. The obtained propylene-ethylene random copolymer (A-4) is MFR A The concentration was 7.0 g / 10 min, and the ethylene content was 3.0 mass%.
[0048] [Ethylene-α-olefin copolymer (B-1)] Density is 903 kg / m³ 3 MFR B The amount is 4.0g / 10min (manufactured by Prime Polymer, product name: SP0540 metallocene catalyst).
[0049] [Ethylene-α-olefin copolymer (B-2)] Density is 903 kg / m³ 3 MFR B The recommended dosage is 15g / 10min (manufactured by Prime Polymer, product name: SP00206, metallocene catalyst).
[0050] [Ethylene-α-olefin copolymer (B-3)] Density is 893 kg / m³ 3 MFR B The amount is 18g / 10min (manufactured by Mitsui Chemicals, product name: A-20090S metallocene catalyst).
[0051] [Ethylene-α-olefin copolymer (E-1)] Density is 885 kg / m³ 3 MFR B The amount is 18g / 10min (manufactured by Mitsui Chemicals, product name: A-20085S metallocene catalyst).
[0052] [Ethylene-α-olefin copolymer (E-2)] Density is 910 kg / m³ 3 MFR B The recommended dosage is 10g / 10min (Prime Polymer Co., Ltd., product name: NZ10100 Ziegler-type catalyst).
[0053] The physical properties of the propylene-based polymer compositions obtained in the examples and comparative examples were measured by the following method.
[0054] [Measurement of ethylene content in propylene-ethylene random copolymer] 13 1C NMR was performed using the following equipment and conditions. • Measurement device: JEOL LA400 type nuclear magnetic resonance spectrometer • Measurement mode: BCM (Bilevel Complete decoupling) Observation frequency: 100.4MHz Observation range: 17006.8Hz • Pulse width: 45° of the C nucleus (7.8 μsec) • Pulse repetition time: 5 seconds • Sample tube: 5mmφ • Sample tube rotation speed: 12Hz • Total number of times: 20,000 ·Measurement temperature: 125℃ • Solvent: 1,2,4-Trichlorobenzene: 0.35 ml / Deuterated benzene: 0.2 ml • Sample quantity: approximately 40 mg
[0055] From the spectra obtained by measurement, the ratio of monomer chain distribution (triad distribution) was determined in accordance with the following reference (1), and the mole fraction (mol%) of constituent units derived from ethylene (hereinafter referred to as E(mol%)) and the mole fraction (mol%) of constituent units derived from propylene (hereinafter referred to as P(mol%)) were calculated. From the obtained E(mol%) and P(mol%), the mass percent was converted according to the following formula (Equation 1) to obtain the aforementioned D of the propylene polymer. insol and D sol The content (mass%) of constituent units derived from ethylene (hereinafter referred to as E(wt%)) was calculated. E(wt%)=E(mol%)×28×100 / [P(mol%)×42+E(mol%)×28] (Formula 1) Literature (1): Kakugo, M.; Naito, Y.; Mizunuma, K.; Miyatake, T., Carbon-13 NMR determination of monomer sequence distribution in ethylene-propylene copolymers prepared with delta-titanium trichloride-diethylaluminum chloride. Macromolecules 1982, 15, (4), 1150-1152
[0056] [Tensile modulus of elasticity] Type A1 test specimens described in JIS K7139 were molded by injection molding using a propylene polymer composition. After molding, the specimens were left in a constant temperature room adjusted to room temperature of 23±5°C and relative humidity of 50±5% for 72 hours, and then determined in accordance with JIS K 7161 (ISO178).
[0057] [Charpy impact strength] Type A1 test specimens described in JIS K7139 were molded by injection molding using a propylene polymer composition. After molding, they were left in a constant temperature room adjusted to room temperature of 23±5°C and relative humidity of 50±5% for 72 hours, and then determined in accordance with JIS K 7111 (ISO179).
[0058] [High-speed surface impact test (high rate, HRIT (Fracture Energy Injection))] Test machine: Shimadzu HYDRO SHOT HITS-P10 (manufactured by Shimadzu Corporation) • Test specimen: ISO 2mm thick flat plate (80mm x 80mm x 2mm thick) • Method of preparing test specimens: Using an injection molding machine with a clamping pressure of 100 tons, the specimens were injection molded at a molding temperature of 200°C and a mold temperature of 40°C. After being left in a constant temperature room adjusted to room temperature of 23±5°C and relative humidity of 50±5%, the specimens were tested. • Test Method: A test specimen was placed on a support stand (hole diameter 76.2 mm) and struck with a load sensor, a dart (diameter 12.7 mm, flat dart with a flat striking surface), at a speed of 3.0 m / s. The deformation and fracture behavior of the test specimen under impact load was measured, and the impact energy absorbed up to the crack initiation point in the obtained impact pattern was calculated and defined as the impact strength of the material. The measurement ambient temperature was 0 ± 0.5 °C. In this measurement, 1 J was the lower limit of the measurement.
[0059] [Transparency (HAZE)] ISO flat plates with a thickness of 2 mm were formed by injection molding using a propylene polymer composition. After molding, the plates were left in a constant temperature room adjusted to room temperature of 23±5°C and relative humidity of 50±5% for 72 hours, and then measured according to JIS K 7136 (ISO 14782) JIS K 7361-1.
[0060] [Transparency after frame processing] ISO flat plates with a thickness of 2 mm were formed by injection molding using a propylene polymer composition. After molding, the plates were left for 72 hours in a constant temperature chamber adjusted to room temperature of 23±5°C and relative humidity of 50±5%. Then, flame treatment was performed using a gas burner adjusted to produce an inner flame of 25-30 mm, with the sample and the burner nozzle at a distance of approximately 60 mm and the burner moving at approximately 35 mm / s.
[0061] The distance between the document containing the text and the observer (visual inspection) was set to approximately 20 cm. A sample was placed exactly in the middle of this distance, and the transparency was evaluated visually by comparing the sample before and after framing. ○: The transparency remains unchanged, and the text is clearly visible. △: Changes in transparency have been observed, making the text slightly difficult to read. ×: Significant changes in transparency have been observed, making the text illegible.
[0062] [Example 1] 87 parts by mass of propylene-ethylene random copolymer (A-1), 13 parts by mass of the above ethylene-α-olefin copolymer (B-1), and a total of 100 parts by mass of (A-1) and (B-1) were added to a mixture containing 0.30 parts by mass of nonitol 1,2,3-trideoxy-4,6:5,7-bis-O-[(4-propylphenyl)methylene] ("Millard NX8000J" (trade name), manufactured by Milliken) as a nucleating agent, 0.13 parts by mass of tris(2,4-di-t-butylphenyl) phosphite ("Irgafos168" (trade name), manufactured by BASF) as a phosphorus-based antioxidant, 0.10 parts by mass of calcium stearate (manufactured by Nitto Kasei Co., Ltd.) as a neutralizing agent, and 0.04 parts by mass of 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane as a predetermined organic peroxide, and the mixture was stirred and mixed using a Henschel mixer.
[0063] The obtained mixture was melt-kneaded using a twin-screw extruder (TEM35BS) manufactured by Toshiba Machine Co., Ltd. under the following conditions to obtain strands. • Model: TEM35BS (35mm twin-screw extruder) • Screw rotation speed: 300 rpm Screen mesh: #200 ·Resin temperature: 230℃
[0064] The obtained strands were water-cooled and then cut in a pelletizer to obtain a pelletized propylene-based polymer composition. The physical properties of the obtained propylene-based polymer composition were measured using the measurement method described above. The results are shown in Table 1.
[0065] [Examples 2-6, Comparative Examples 1-10] A pelletized propylene polymer composition was obtained by following the same procedure as in Example 1, except that the polymer species listed in Tables 1 and 2 were used instead of the propylene-ethylene random copolymer (A-1) and ethylene-α-olefin copolymer (B-1) used in Example 1. The physical properties of the obtained propylene polymer composition were measured using the measurement method described above. The results are shown in Tables 1 and 2.
[0066] [Table 1]
[0067] [Table 2]
[0068] As is clear from Table 1, injection-molded articles using the propylene-based resin composition obtained by the manufacturing method of the present invention exhibited excellent impact resistance, transparency, and transparency after flame treatment (Examples 1-6).
[0069] On the other hand, as shown in Table 2, Comparative Examples 1 and 7 lacked sufficient or no ethylene-α-olefin copolymer, and Comparative Example 2 did not undergo dynamic heat treatment with organic peroxide, resulting in insufficient impact resistance. Comparative Examples 3, 4, 8, 9, and 10 did not satisfy formula (1), resulting in insufficient transparency after flame treatment. Comparative Examples 5 and 6 had ethylene-α-olefin copolymer densities outside the specified range, resulting in insufficient transparency. [Industrial applicability]
[0070] The propylene-based resin composition obtained by the manufacturing method of the present invention exhibits excellent rigidity and impact resistance while maintaining transparency, and in particular, does not impair transparency after frame treatment. Furthermore, injection-molded articles obtained using this polypropylene-based resin composition exhibit excellent transparency, rigidity, and impact resistance, and do not impair transparency after frame treatment, making them suitable for use in distribution materials requiring labeling or printing, food containers, various beverage containers, medical containers, etc., thus possessing significant industrial value.
Claims
1. Ethylene content of 1-5% by mass, melt flow rate (MFR) conforming to JIS K7210 (temperature: 230°C, 2.16 kg load) A 80 to 91 parts by mass of a propylene-ethylene copolymer (A) having a concentration in the range of 0.1 to 50 g / 10 min, Furthermore, the density is 890-909 kg / m³ 3 Melt flow rate (MFR) conforming to JIS K7210 (temperature: 190°C, 2.16 kg load) B A mixture containing 9 to 20 parts by mass of an ethylene-α-olefin copolymer (B) (where propylene is removed from the α-olefin) having a concentration in the range of 1 to 50 g / 10 min [where the total amount of (A) + (B) is 100 parts by mass], The mixture consists of the propylene-ethylene copolymer (A), the ethylene-α-olefin copolymer (B), and at least one additive selected from the group consisting of nucleating agents, antioxidants, ultraviolet absorbers, neutralizing agents, light stabilizers, antistatic agents, antiblocking agents, lubricants, odor adsorbents, antibacterial agents, pigments, inorganic fillers, and organic fillers, which may be added as needed. The mixture, Dynamic heat treatment with organic peroxides is performed to obtain a melt flow rate (MFR) in accordance with JIS K7210 (temperature: 230°C, 2.16 kg load). C A method for producing a propylene polymer composition (C) wherein the following formula 1 is satisfied and the amount is in the range of 1 to 100 g / 10 min. (MFR C )-(MFR A )≦2×(MFR B )...Equation (1)
2. A method for producing a propylene polymer composition (C) according to claim 1, wherein the mixture contains a nucleating agent.
3. The MFR of the propylene-ethylene copolymer (A) A is in the range of 0.1 to 30 g / 10min, and the MFR of the ethylene-α-olefin copolymer (B) B is in the range of 1 to 30 g / 10min, The organic peroxide is contained in an amount of 0.005 to 0.12 parts by mass [provided that the total amount of (A) + (B) is 100 parts by mass], The MFR of the propylene polymer composition (C) C A method for producing the propylene polymer composition (C) according to claim 1, wherein the amount is in the range of 1 to 40 g / 10 min.
4. A method for producing an injection-molded article, comprising injection molding a propylene polymer composition (C) obtained by a method for producing a propylene polymer composition (C) according to any one of claims 1 to 3.
5. A method for manufacturing an injection-molded article according to claim 4, wherein the injection-molded article is subjected to frame processing.
Citation Information
Patent Citations
Producing method of propylene resin composition
JP2004176061A
Polypropylene resin composition and molding
JP2009019119A
Polypropylene resin composition and molded article
JP2009155422A
Polypropylene resin composition, and film produced thereby
JP2012236973A
Polypropylene resin composition and resin molded product
JP2016108509A